DESIGNING A TASK-BASED ENGLISH COURSE BOOK FOR STUDENTS OF FOOD CROPS AT POLITAN - Resa Yulita (Universitas Negeri Padang, 2016)
Students of multilingual speakers need a good course book to help them improve their performance in English language. A good course book means a book that can fulfill student’s needs as well as relevant with the curriculum of the course. From need and situation analysis, it was found that, Politani students need a book which is interesting and communicative. Unfortunately, the present course book does not fulfill their needs. Aside from that, the present course book was also not relevant with the curriculum used. As the result, most of students have a poor performance in English. They have difficulty in using English as means of communication. On the basis of these phenomena, an R and D research was conducted by using four-D model. This model consists of define, design, develop and disseminate stages. Due to limited time, in this research, disseminate stage was not conducted. The aim of the research is to produce a new course book which was designed by using Task-Based Approach. This approach is considered to be one of communicative approaches. The book was designed to be used by semester II student of Food Crops study program. The result of the research shows that the book is valid and practical to be used for students of semester II Food Crops study program at Politani.